Cultural Tourism Development Model for Local Community Livelihoods: Indigenous Peoples - Rahmawati, Rita; Pratidina, Ginung; Mulyono, Imam Edy; Rusliandy; Heryati, Ade; Hernawan, Denny; Subagdja , Oetje (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to develop tourism in the Mount Halimun Salak National Park (MHSNP) by highlighting the cultural traditions of the Local Communities. It's expected to be able to overcome the problems around the national park regarding the loss of local people's livelihoods by building new livelihoods in the tourism sector. However, tourism activities in this national park have not fully had a positive impact on increasing national park income and community welfare, as well as the limited involvement of local communities and other stakeholders in tourism activities. The method used in this study is a qualitative research method with a hermeneutic approach with data collection techniques through literature studies, field observations, in-depth interviews, and FGDs. The results of the study show that there are local wisdom, values in the Kasepuhan Indigenous Peoples derived from heritage values. Local culture is passed down from generation to generation, while in the Sukagalih community, they developed local wisdom from new institutions prepared by the Mount Halimun Salak National Park Office in the conservation village program. The results of the study also formulated a model of tourism development based on local cultural values. This model requires institutional development and human resource development. The availability of skilled human resources, budgets, and infrastructure are the main supporting factors for managing local cultural values, which previously only functioned as doctrines as developmental potential